Davlat sektorida buxgalteriya hisobining kassa metodini qo`llashning nazariy-amaliy jihatlari - Masharipov Odilbek Muzaffar o‘g‘li (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2025)
This article discussed the importance of the process of using the cash method of accounting in the public sector of the Republic of Uzbekistan, substantiating the theoretical and practical aspects of its priorities and shortcomings, and further improving the budget and accounting in our country through the achievements of the cash method based on international experience and standards.